2022
DOI: 10.9734/cjast/2022/v41i1831738
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Financial Performance of the Microfinance Institutions in Tamil Nadu

Abstract: Aims: To study and analyze the major determinants of financial performance of the microfinance institutions in Tamil Nadu. Study Design:  Purposive Random Sampling method was used. Both primary and secondary data was used for the analysis. Place and Duration of Study: In Tamil Nadu, Coimbatore district was purposively selected for the study. Survey was conducted for the collection of primary data pertaining to the period of 2021-22 and also secondary data was collected for the period of 2010-2019 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Thus, the financial performance of MFIs is important. Empirical evidence (Dissanayake, 2012;Ngumo et al, 2017;Rani et al, 2022;Shkodra, 2019) showed that various internal and external factors have a significant influence on the financial performance of MFIs. Thus, the financial manager of MFI needs to identify the major factors that influence their financial performance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the financial performance of MFIs is important. Empirical evidence (Dissanayake, 2012;Ngumo et al, 2017;Rani et al, 2022;Shkodra, 2019) showed that various internal and external factors have a significant influence on the financial performance of MFIs. Thus, the financial manager of MFI needs to identify the major factors that influence their financial performance.…”
Section: Introductionmentioning
confidence: 99%